2015
DOI: 10.1002/ijc.29827
|View full text |Cite
|
Sign up to set email alerts
|

No role for human papillomavirus infection in oral cancers in a region in southern India

Abstract: Oral cancer is a major public health issue in India with~77,000 new cases and 52,000 deaths yearly. Paan chewing, tobacco and alcohol use are strong risk factors for this cancer in India. Human papillomaviruses (HPVs) are also related to a subset of head and neck cancers (HNCs). We examined the association between oral HPV and oral cancer in a sample of Indian subjects participating in a hospital-based case-control study. We recruited incident oral cancer cases (N 5 350) and controls frequencymatched by age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 25 publications
1
30
1
Order By: Relevance
“…Where exome sequence was available, the absence of HPV was re-confirmed using HPVDetector, as previously described [16]. TSCC samples of Indian origin to be HPV negative is consistent with other studies [17-19]. …”
Section: Resultssupporting
confidence: 63%
“…Where exome sequence was available, the absence of HPV was re-confirmed using HPVDetector, as previously described [16]. TSCC samples of Indian origin to be HPV negative is consistent with other studies [17-19]. …”
Section: Resultssupporting
confidence: 63%
“…However, some studies showed that HPV DNA was not detected in the oral cancers or controls. This may reflect specific cultural or religious characteristics …”
Section: Discussionmentioning
confidence: 99%
“…In northeastern Thailand, HPV DNA was detected in about 13% of exfoliated buccal cell samples from the normal population . By contrast, in South India, HPV DNA was not found in normal oral mucosal samples, nor in epithelium cells from the sites of oral cancers …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations